The anatomy of the inferior mesenteric artery: a systematic review with meta-analysis. - Triantafyllou, George; Belimezakis, Nektarios; Lyros, Orestis; Arkadopoulos, Nikolaos; Demetriou, Fotis; Tsakotos, George; Piagkou, Maria (Surgical & Radiologic Anatomy, 2025)
Purpose: This evidence-based systematic review with meta-analysis aims to synthesize the inferior mesenteric artery (IMA) variants including their origin level, branching patterns, and morphometric characteristics. Materials and methods: The study adhered to the latest guidelines. Four online databases were used for the systematic review, and studies that reported the prevalence of IMA variants were considered eligible for inclusion. A statistical meta-analysis was conducted using R programming software with a random-effects model to calculate the pooled prevalence of the variants. Results: Twenty-three (23) studies were included in this analysis. The IMA typically originated at the 3rd lumbar vertebra (L3) level, occurring in 70.16% of cases. The most common branching pattern of the IMA was bifurcated, indicating a pooled prevalence of 63.89%. This predominant pattern involved the IMA bifurcating into the left colic artery (LCA) and a common trunk for both the superior rectal artery (SRA) and the sigmoid artery (SA), with a pooled prevalence of 46.09%. The IMA trifurcation and tetrafurcation had pooled prevalences of 27.35% and 11.62%, respectively. The diameter of the IMA had a pooled mean of 41.41 mm, and the distance from the IMA's origin to the LCA had a pooled mean of 40.67 mm. Conclusions: This review of existing literature delineates the IMA levels of origin, branching patterns, and morphometric characteristics. A comprehensive understanding of the surgical anatomy of this vessel is imperative during colorectal cancer procedures. Consequently, surgeons operating in this anatomical region must possess an in-depth knowledge of typical and variant anatomical structures.